1977
DOI: 10.1007/bf00439095
|View full text |Cite
|
Sign up to set email alerts
|

Brain monoamine oxidase activity after chronic ethanol treatment of rats

Abstract: Rats were given chronic treatments with ethanol in two ways: by offering 10% ethanol in water as the only liquid supply for 34 weeks and by exposing the rats to ethanol vapour during 5 h daily for 7 weeks. In this way blood ethanol levels of 1.4-2.3 and 5.5-6.9 mg/ml, respectively, were accomplished. In neither of the cases was brain monoamine oxidase activity changed. The result supports an hypothesis previously advanced that the lowered monoamine oxidase activity found in the brain of a suicide patient was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Platelet monoaminooxidase (MAO) activity was also found to be lower in some studies (Oreland, 1980), recovering its activity after 4 weeks of abstinence (Takahashi, 1976). Post-mortem investiga-tion demonstrated also decreased MAO activity in the brain of alcoholic suicides (Got#ries, 1975), although there are controversies in this field regarding both MAO activity (Wiberg, 1977) and 5-HT concentration of the brain (Cochran, 1976).…”
Section: Introductionmentioning
confidence: 95%
“…Platelet monoaminooxidase (MAO) activity was also found to be lower in some studies (Oreland, 1980), recovering its activity after 4 weeks of abstinence (Takahashi, 1976). Post-mortem investiga-tion demonstrated also decreased MAO activity in the brain of alcoholic suicides (Got#ries, 1975), although there are controversies in this field regarding both MAO activity (Wiberg, 1977) and 5-HT concentration of the brain (Cochran, 1976).…”
Section: Introductionmentioning
confidence: 95%
“…Wiberg et al have also reported that chronic ethanol treatment in rats did not alter brain MAO activity (19).…”
Section: Discussionmentioning
confidence: 96%
“…The early demonstration of diminished MAO activity in brains of alcoholic suicide victims [88], and the more recent work on human brain MAO activity by Oreland et al [89], gener ated speculation as to whether the lower MAO activity in brain tissue from alcoholics was a result of alcohol abuse, or an inherent characteristic of the individual. Studies of brain MAO activity in rats fed ethanol for up to 34 weeks indicated that ethanol produced little change in the brain MAO activity [90]. MAO activity was also unaltered in brains of mice made physically dependent on ethanol [91].…”
Section: Ac Activity After Chronic Ethanol Treatmentmentioning
confidence: 99%
“…As described above, chronic ethanol in gestion was reported not to alter brain MAO activity [90,91], However, the selective in vitro action of ethanol on MAO-B suggests that changes may occur only in one form of the brain enzyme after chronic ethanol treat ment, and this possibility should be investi gated in more detail.…”
Section: Effect Of Ethanol On Amine Oxidasementioning
confidence: 99%